Verifying conservation estimates for on-farm agricultural water conservation programs - Ramirez, Ana, author; Pandey, Stacy, author; Eaton, David, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
This paper presents an update on the statistical analysis of water use practices on precision leveled rice fields irrigated by the Lower Colorado River Authority (LCRA) Lakeside Irrigation Division. Results from the 2011 analysis confirms again that there is a statistically significant difference in water use between leveled and non-leveled fields (0.33 acre feet of water savings per acre farmed for the first rice crop only). The updated study incorporated and/or refined several additional variables that affect field water use such as other on-farm conservation measures and management practices of individual producers, added a year of data, and will include a separate analysis of the effect of system-wide savings on river diversions. The analysis used a statistical model that incorporated water use and farm practice data over a 4-year period. This study is a conservation verification component of LCRA's HB 1437 Agriculture Water Conservation Program. LCRA partnered with the LBJ School of Public Affairs at the University of Texas to develop the statistical model and analysis presented in this paper. The House Bill 1437 (HB 1437) Agriculture Water Conservation Program is an innovative way to meet rising municipal demands in Williamson County (located in the Colorado River Basin of Texas), conserve river water used for irrigation, and maintain agriculture productivity. A 2005 implementation study identified land leveling as the first strategy that should be pursued using the funds from this program. The land leveling grant program began in 2006 and from 2006-2010 has funded up to a 30% cost share to precision level 22,086 acres of farm land irrigated with surface water from LCRA. To date an estimated 7,100 acre-feet of water has been conserved as a result of these precision land leveling grants. This study is essential to confirm the accuracy of the water savings estimates, which are being used to calculate the water available for transfer to meet municipal demands. The updated HB1437 short-term plan established a goal of conserving 10,000 acre feet per year by 2014.
Irrigated agriculture responds to water use challenges
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.